Analisis Faktor yang Berhubungan dengan Perilaku Deteksi Dini Kanker Serviks pada Akseptor KB - M, Minanton; Rosa, Serly; Oktavia, Leli Rezky Dwi; Rahagia, Rasi (Citra Delima Scientific journal of Citra Internasional Institute, 2024)
Cervical cancer can be prevented through early detection, but cancer is still one of the main causes of death worldwide. A number of factors may contribute to early detection of cervical cancer in women. The aim of this research was to determine the factors associated with early detection behavior of cervical cancer in women who use contraception. Method: This research is a cross-sectional study with a total of 43 participants using consecutive sampling. Women who come to the gynecology clinic were aged between 15 and >45 years at RSPAL Dr Ramelan Surabaya. Chi-square test to test the relationship between independent and dependent variables. Results: The majority of respondents were between 25-34 years old, 69.7%, with a screening rate of only 32.6%. Factors related to women carrying out early detection of cervical cancer are knowledge (0.009), attitude (0.017) and the role of health workers (0.002). Conclusion: There is a significant relationship with early detection behavior for cervical cancer which includes knowledge, attitudes and the role of health workers. Health workers have an important role as the main source of information about screening/early detection of cervical cancer. In this way, they can increase women's knowledge and positive attitudes regarding early detection of cervical cancer in Indonesia.